Human Trafficking Menurut Perspektif Hukum Islam - Gilang Rizki Aji Putra (ADALAH, 2022)
Trafficking in Persons is "the act of recruiting, transporting, harboring, transmitting, transferring, harboring or receiving persons using the threat of force, use of force, of abduction, of abduction, of fraud, of deception, of the abuse of power or a position of vulnerability, or of providing for the payment of debts or benefits to achieve consent. from people who have control over other people, whether carried out within the country or between countries, for exploitation or leading to exploitation.” Considering that Human Trafficking is a crime against humanity that cannot be tolerated.